2011
DOI: 10.3109/02813432.2011.629150
|View full text |Cite
|
Sign up to set email alerts
|

Safety of telephone triage in out-of-hours care: A systematic review

Abstract: Objective .Telephone triage in patients requesting help may compromise patient safety, particularly if urgency is underestimated and the patient is not seen by a physician. The aim was to assess the research evidence on safety of telephone triage in out-of-hours primary care. Methods. A systematic review was performed of published research on telephone triage in out-of-hours care, searching in PubMed and EMBASE up to March 2010. Studies were included if they concerned outof-hours medical care and focused on te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
155
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(164 citation statements)
references
References 42 publications
2
155
0
2
Order By: Relevance
“…No substantive new research examining the effects of telephone triage for acute care on in-hours primary care workload, resource use, safety or patient experience has been reported during the course of this trial (although new evidence on the safety of telephone triage in out-of-hours care may be pertinent 68 ). Much of this literature is summarised in a systematic review by Bunn et al 27 undertaken in 2005.…”
Section: Research Findings In Contextmentioning
confidence: 99%
“…No substantive new research examining the effects of telephone triage for acute care on in-hours primary care workload, resource use, safety or patient experience has been reported during the course of this trial (although new evidence on the safety of telephone triage in out-of-hours care may be pertinent 68 ). Much of this literature is summarised in a systematic review by Bunn et al 27 undertaken in 2005.…”
Section: Research Findings In Contextmentioning
confidence: 99%
“…The results from the eight reviews (10 papers [57][58][59][60][61][62][63][64][65] ) are shown in Table 4. Many of the references included in the reviews overlapped.…”
Section: Systematic Reviews Includedmentioning
confidence: 99%
“…The related systematic review by Huibers et al 62 included 10 of the papers identified in this review 66,73,74,77,78,82,[89][90][91][92] and reported that a high proportion (97%) of all OOH telephone triage contacts were safe but that the proportion of safe contacts decreased when looking at high-urgency patients. From 10 studies using high-risk simulated patients, the authors found that just 46% were safe, bringing into question whether telephone triage and advice is as safe for higher-urgency patients.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Telephone contact is used variably for assessment and triage of acute problems; [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] general practice consultations; [34][35][36][37][38][39][40] to offer health education; 41,42 and to offer support for those with chronic illness 43,44 or those in need of palliative care. 45 The literature on telephone consultations consists largely of small and heterogeneous primary studies, most of which had practical challenges or methodological flaws.…”
Section: Telephonementioning
confidence: 99%